Avaliação do sistema de gestão dos recursos hídricos em Angola - Zeca, Manuel Francisco (2013)
The Water Resources Management of any country is based on a specific public policy and includes an organizational structure that can plan and manage actions, define the responsibilities, practices and procedures, for the control on the use and impact of actions on water resources. In Angola, country in the western of Southern Africa, the water potential is extensive and diverse. However, the Water Resource Management System (WRMS) is not very fully implemented yet, fact that causes an inefficient water distribution. Thus, this paper analyses what’s necessary to adequate Angola's WRMS to the other countries evaluation index. The Countries were chosen on the basis of: geographical proximity, cultural, economic and social attributes, to have solids colonizing countries of different regions of Africa, and the policy water resources already established: Botswana, Mozambique, Cimabue, Germany, Brazil, France, United States of America and Portugal. The research is quality due problems with the attributes and nature of the study. It evolves raising a documental bibliography that can be applied to the case in Angola. This research happened in three stages. Initially, a model of WRMS from Angola and the other countries was presented. The second stage was made to evaluate the WRMS models using the following evaluation criteria: legal, institutional, conceptual and management mechanism, all also evaluate by qualitative criteria. The third stage determined the Water Resources Management Index (WRMI) and thought it was also possible to establish the strengths and weaknesses the opportunities and threats of Angola's WRMS. The Study's conclusion is that Angola's WRMS performance is weak if compared to the other countries studied. After evaluation, some propositions were made, among them: the public agencies established by the Law of Waters of Angola nº 06/2002 an by Resolution of the Council of Ministers nº 10/2004, such as a Court of Water and some local authorities to control the management of water, considering the different uses of it, and to establish the watershed as a Unit of management. New studies and researches are highly recommended in order to better evaluate Angola's WRMS.